KOMUNIKASI INTERPERSONAL DI LINGKUNGAN KERJA APARTMENT THE SUITES METRO - Syevira, Syevira (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2021)
The success of the company is determined by a good work ethic carried out by employees, because employees are an important organ that can affect the company's rating. In this case, the work environment at the Metro Suites Apartment applies the concept of good interpersonal communication which may contain prophetic value as an initial assumption. So the purpose of this study is to review whether the prophetic value is contained in the interpersonal communication of employees in the work environment at the Metro Suites Apartment. This paper applies a case study method based on a qualitative approach. Thus the results of the study obtained are to find the interpersonal communication style in the work environment at the Metro Suites Apartment contains elements of prophetic values in it, namely the value of amar ma'ruf which means humanist, and the value of nahyi munkar means preventing liberation. Keywords : Interpersonal Communication, Employees, Prophetic.